Method for the height measurement of agricultural implements based on variable parameter Kalman filter - Chen, Gaolong; Luo, Xiwen; Hu, Lian; Wang, Pei; He, Jie; Feng, Dawen; Li, Weicong; Jiao, Jinkang (International Journal of Agricultural and Biological Engineering, 2024)
To improve the GNSS receiver’s accuracy, continuity, and stability in measuring the height of agricultural implements, this study proposed a variable-parameter Kalman filter (VPKF) algorithm based on GNSS and accelerometer to estimate the height of the implements optimally. The VPKF was verified, and its accuracy was evaluated by parallel rail platform and field tests. From the parallel rail test results, when the GNSS receiver was in real-time kinematic (RTK) positioning and the time delay of differential correction data (TDDCD) was less than or equal to 4 s, the root mean square error (RMSE) of the VPKF estimation was 9.82 mm. The RMSE of the GNSS measurement was 18.85 mm. When the GNSS receiver lost differential correction data within 28 s, the absolute error of VPKF was less than 30 mm, and the RMSE was 16.93 mm. The field test results showed that when the GNSS receiver was in RTK positioning and the TDDCD was less than or equal to 4 s, the RMSE of VPKF estimation was 13.43 mm, and the GNSS measurement was 14.56 mm. When the GNSS receiver lost differential correction data within 28 s, the RMSE of the VPKF estimate was 15.22 mm. These results show that VPKF can optimally estimate implement height with better accuracy. Overall, the VPKF can obtain a more accurate, continuous, and stable height of the implement, and increase the application scenarios of the GNSS receiver to measure the implement height. Key words: agricultural implement, height, Kalman filter, GNSS, accelerometer [DOI] 10.25165/j.ijabe.20241702.8026 Citation: Chen G L, Luo X W, Hu L, Wang P, He J, Feng D W, et al. Method for the height measurement of agriculturalimplements based on variable parameter Kalman filter. Int J Agric & Biol Eng, 2024; 17(2): 193–199.